Os recursos linguísticos no projeto de desliteraturização de Monteiro Lobato: discutindo a obra fábulas - Rocha, Michele Saionara Aparecida Lopes de Lima [UNESP] (Universidade Estadual Paulista (Unesp), 2015)
The research presented is a retelling of the book Fábulas, while the objective is to discuss the Monteiro Lobato's project of desliteraturização in children literature and raise the linguistic features present in the work that may characterize this project. The study was conducted with a qualitative approach, from bibliographical research, contemplating the reading of academic documents, literary works, writings authored by Monteiro Lobato, biographical works of the writer and works of scholars on the stylistic and semantic portuguese language. From the rereading of the work, it was revealed Lobato, in writing the book, was concerned to bring the written language of oral features and wrote Fábulas in a desliteraturizada language while consists of the following linguistic resources: phraseologism (idiomatic expressions and popular sayings), diminutives, augmentative, superlatives, neologisms, onomatopoeia and synecdoches. These linguistic features utilized by Lobato are an important contribution to the development of literature in Brazil that contemplates at infant public and the brazilian reality

A pesquisa que se apresenta é uma releitura do livro Fábulas, com o objetivo de discutir o projeto de desliteraturização de Monteiro Lobato na literatura infantil e levantar os recursos linguísticos presentes na obra que possam caracterizar esse projeto. O estudo foi realizado com uma abordagem qualitativa, a partir de pesquisa bibliográfica, contemplando a leitura de trabalhos acadêmicos, obras literárias, escritos de autoria de Monteiro Lobato, obras biográficas do escritor e trabalhos de estudiosos sobre a estilística e semântica da língua portuguesa. A partir da releitura da obra foi possível perceber que Lobato, ao escrever o livro, preocupou-se em aproximar a linguagem escrita da linguagem oral e escreveu Fábulas em uma linguagem desliteraturizada composta pelos seguintes recursos linguísticos: fraseologismo (expressões idiomáticas e ditados populares), diminutivos, aumentativos, superlativos, neologismos, onomatopeias e sinédoques. Estes recursos linguísticos utilizados por Lobato são uma importante contribuição para o desenvolvimento de uma literatura no Brasil que contemple o público infantil e a realidade brasileira
Keywords: Children's literature; Lobato, Monteiro, 1882-1948; Literatura infantojuvenil; Fábulas; Linguística; Fraseologia